Comprehensive analysis of current epidemiology, clinical features and Prognostic Factors of puerperal endometritis: A retrospective cohort analysis - Rafael San-Juan; Alba Sanz-Prieto; Javier Contreras-Mora; Iván Fojo-Suárez; José María Caso-Laviana; Mario Fernández-Ruiz; Francisco López-Medrano; Isabel Rodríguez-Goncer; Marina Fayos; Patricia Brañas; P. Barbero Casado; Antonio García-Burguillo; et al. (Elsevier, 2023)
Background: Puerperal endometritis has not been recently investigated. We aimed to describe the current dimension of the endometritis in the context of other causes of puerperal fever and investigate the microbiology and need for curettage in these patients Methods: A retrospective cohort study was conducted based on a prospectively maintained database of patients with puerperal fever, (2014-2020) in which cases fulfilling criteria for endometritis were selected for further analysis. Description of clinical and microbiological features was performed and determination of the factors related with puerperal curettage requirement were studied using univariate and multivariate analysis through binary logistic regression. Results: From 428 patients with puerperal fever, endometritis was the main cause of puerperal fever (233 patients, 52.7 %). Curettage was required in 96 of them (41.2 %). Culture of endometrial samples were performed in 62 (64.5 %), of which 32 (51.6 %) yielded bacterial growth. Escherichia coli was the most common microorganism in curettage cultures (46.9 %). Multivariate analysis identified the following predictive factors for curettage: the presence of pattern compatible with retained products of conception (RPOC) in transvaginal ultrasonography (odds ratio [OR]: 17.6 [95 % confidence interval [CI]: 8.4-36.6]; P-value < 0.0001), fever during the first 14 days after delivery (OR:5.1; [95 % CI: 1.57-16.5]; P-value 0.007), abdominal pain (OR: 2.9; [95 % CI: 1.36-6.1]; P-value 0.012) and malodorous lochia (OR:3.5; [95 % CI: 1.25-9.9]; P-value 0.017). Scheduled cesarean delivery was protective (OR: 0.11 [95 % CI 0.01-1.2]; P-value 0.08). Conclusions: Endometritis is still the main cause of puerperal fever. Women requiring curettage typically presented with abdominal pain and foul-smelling lochia, an ultrasound image compatible with RPOC and fever in the first 14 days postpartum. Curettage culture is useful for the microbiological affiliation mostly yielding gram-negative enteric flora.